New Challenges in Airport Business - Lowden, Ian (Henry Stewart Talks, 2009)
Current global economic market, Airport finances, Key issues and trends, Relationship between traffic and revenue growth, Retail is key to commercial revenue growth, Airline and airport behavior, Characteristics of fast growing UK airports, Who are the competitors?, Understanding the market, IT and CRM, Tourism and regional relationships, Defining your product